2019
DOI: 10.12688/f1000research.19766.3
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing of microbial cell-free DNA for rapid noninvasive diagnosis of infectious diseases in immunocompromised hosts

Abstract: Background: Cell-free DNA (cfDNA) sequencing has emerged as an effective laboratory method for rapid and noninvasive diagnosis in prenatal screening testing, organ transplant rejection screening, and oncology liquid biopsies but clinical experience for use of this technology in diagnostic evaluation of infections in immunocompromised hosts is limited.  Methods: We conducted an exploratory study using next-generation sequencing (NGS) for detection of microbial cfDNA in a cohort of ten immunocompromised patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…To date, there have been 5 reports on successful use of mNGS to diagnose pulmonary infections involving P. jirovecii (Table 2). [14][15][16][17][18] While the sample size is small (1 to 13 specimens each), these studies involve the use of different types of specimens (BALF, sputum, lung biopsy and blood) and different NGS platforms. The numbers of sequence reads for P. jirovecii are highly variable (2 to 303,572) among studies though all are less than the P. jirovecii reads identified from our case (1,665,693).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been 5 reports on successful use of mNGS to diagnose pulmonary infections involving P. jirovecii (Table 2). [14][15][16][17][18] While the sample size is small (1 to 13 specimens each), these studies involve the use of different types of specimens (BALF, sputum, lung biopsy and blood) and different NGS platforms. The numbers of sequence reads for P. jirovecii are highly variable (2 to 303,572) among studies though all are less than the P. jirovecii reads identified from our case (1,665,693).…”
Section: Discussionmentioning
confidence: 99%
“…This method has been successfully used as a diagnostic tool for various infectious diseases including PCP. [14][15][16][17] Its application to diagnose PCP in renal transplant recipients has been attempted in one study, 18 and its value awaits further evaluation. Here we report a case of PCP diagnosed by mNGS following negative results in multiple conventional diagnostic tests.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study by Grumaz et al revealed that the rate of positive mNGS results was constant over the different time points after sepsis developed, while the positivity of blood culture decreased at later time points [28]. Camargo et al indicated that cell-free DNA sequencing could still identify fungus such as P. jirovecii or Aspergillus species among patients receiving effective antifungal agents [29]. Another study by Miao et al also revealed that mNGS is less affected by prior antibiotic exposure, which showed opposite findings to our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Less-expensive molecular assays for detection of P. jirovecii, such as loop-mediated isothermal amplification, is an alternative [37]. Recently, the next generation sequencing (NGS) and measurement of P. jirovecii-free DNA from peripheral blood showed promising results in immunocompromised hosts [38]. Molecular assays have increased detection rates of P. jirovecii, but the wide use of these methods is limited probably due to economic reasons, low incidence of PcP, and sometimes false positive results.…”
Section: Discussionmentioning
confidence: 99%